Pengaruh Konsep Diri Terhadap Perilaku Konsumtif Mahasiswa - Gracela Natasha Luas; Sapto Irawan; Yustinus Windrawanto (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2023)
Consumptive behavior is often associated with a luxurious and excessive life and a pattern of life that is driven by a desire other than to seek pleasure and follow emerging trends. The factor influencing consumptive behavior is self-concept, where there are individual associations in a group that cause the desire to buy goods. This research method uses quantitative research methods using an instrument in the form of a questionnaire. The researcher conducted an instrumentation test, namely a self-concept questionnaire and a consumptive behavior questionnaire on Monday, October 3, 2021 at SWCU with 33 respondents who were randomly selected. Based on the research and discussion that has been done, it can be concluded that there is a significant influence of self-concept on the consumptive behavior of SWCU BK students class of 2019. This is evidenced by the R square value of 0.097 or 9.7%, which means that self-concept has an influence of 0.097 or 9.7% with consumptive behavior.